Casual association between social determinants of health and sexual health literacy in reproductive-aged women: a WHO model analysis - Fatemeh Vakili; Malihe Nasiri; Zeinab Hamzehgardeshi; Shayesteh Jahanfar; Zohreh Mahmoodi; Seideh Hanieh Alamolhoda (BMC Public Health)
Abstract Introduction Sexual health literacy is an important factor affecting sexual health, and social determinants of health significantly increasing health literacy. This study aimed to investigate the relationship between social determinants of health and sexual health literacy. Method The present cross-sectional study was conducted on 600 married women of reproductive age referred to health centers in Tehran, Iran (2024). Questionnaires included demographic and obstetric details, Perceived Social Support, Socioeconomic Status, and Intimate Partner Violence. The statistical analysis was performed in SPSS-27, and the relationship model was examined using the path analysis method in LISREL-8.8. Results According to the path analysis, sexual health literacy was directly affected by domestic violence (B = -0.12) and perceived social support (B = 0.39). It was also indirectly affected by socioeconomic status (B = 0.44) and spouse education (B = 0.48). Conclusion The results showed that some factors influence sexual health literacy in women both directly and indirectly. Given the factors identified in the suggested model, it is advisable to utilize this model as a suitable framework for research, design, and execution of initiatives concerning sexual health literacy.